Evaluasi Pelaksanaan Pemungutan Pajak Bumi Dan Bangunan Pedesaan Dan Perkotaan Di Kota Bekasi Tahun 2021 - Ahmad Kasyfi Badri Ali; Dwikora Harjo (Jurnal Ilmu Administrasi Publik, 2023)
This study aimed to find out the evaluation of the collection of Urban Rural Land and Building Tax (PBB-P2) in Bekasi City in 2021 by using a qualitative descriptive method.The data collection was carried out through field observations at the Bekasi City Regional Revenue Agency (Bependa) office; interviews with informants consisting of the Head of the Tax Collection and Retribution Sub- Section for Bapenda Bekasi City, Academic Lecturers at the Institute of Social Sciences and Management Stiami, and three taxpayers; and documentation. The theory employed was Bridgman & Davis (2000). The measurements of public policy evaluation generally refer to four main indicators, namely: (1) input indicators, (2) process indicators, (3) output indicators, and(4) outcomes indicators. The results of this study, related to the evaluation of the implementation of the Bekasi Urban Rural Land and Building Tax collection, showed that there were still many people who had not been socialized and knew about the payment procedures for Regulation of Mayor of Bekasi City No. 53 of 2019. Then, the obstacle experienced was the people have not been educated about the payment of Rural and Urban Land and Building Tax. Finally, the effort made by the Government of Bekasi City was working with various agencies to conduct socialization to the people of Bekasi City.This study aimed to find out the evaluation of the collection of Urban Rural Land and Building Tax (PBB-P2) in Bekasi City in 2021 by using a qualitative descriptive method.The data collection was carried out through field observations at the Bekasi City Regional Revenue Agency (Bependa) office; interviews with informants consisting of the Head of the Tax Collection and Retribution Sub- Section for Bapenda Bekasi City, Academic Lecturers at the Institute of Social Sciences and Management Stiami, and three taxpayers; and documentation. The theory employed was Bridgman & Davis (2000). The measurements of public policy evaluation generally refer to four main indicators, namely: (1) input indicators, (2) process indicators,(3) output indicators, and(4) outcomes indicators. The results of this study, related to the evaluation of the implementation of the Bekasi Urban Rural Land and Building Tax collection, showed that there were still many people who had not been socialized and knew about the payment procedures for Regulation of Mayor of Bekasi City No. 53 of 2019. Then, the obstacle experienced was the people have not been educated about the payment of Rural and Urban Land and Building Tax. Finally, the effort made by the Government of Bekasi City was working with various agencies to conduct socialization tothe people of Bekasi City.